Look Who’s Asking—Reflections on Participatory and Transdisciplinary Marine Research Approaches - Breckwoldt, Annette; Lopes, Priscila F. M.; Selim, Samiya A. (Frontiers in Marine Science, 2021)
Oftentimes marine conservation transdisciplinary researchers get to the field with a previously designed question. Once in the field, they may or may not have the support of local communities to sample their data, although they will regularly need to count on these same communities if some sort of collaborative regime is to be pursued and informed by the researchers’ outcome. However, involving people on the ground (i.e., coastal communities themselves and smaller grassroots organizations) in the initial phase of asking the questions and setting the research agenda is still uncommon. Research questions are often formulated outside the actual geographical, social, cultural and ecological setting in which the research projects are supposed to be anchored. Despite some advances, the direction of the information flow still seems predominantly one way. Knowing who is asking the questions and assuring that all stakeholders have a voice in this process becomes especially relevant under extreme circumstances (e.g. disasters, pandemics), when problems are plenty but can only be accessed by those on the ground. Faster progress in transforming academic and funding environments for true ‘level-playing-field’ transdisciplinary and co-designed research projects needs to lever this persisting mono-directional research tendency.